The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/cddis.2013.13
|View full text |Cite
|
Sign up to set email alerts
|

Conformational altered p53 affects neuronal function: relevance for the response to toxic insult and growth-associated protein 43 expression

Abstract: The role of p53 in neurodegenerative diseases is essentially associated with neuronal death. Recently an alternative point of view is emerging, as altered p53 conformation and impaired protein function have been found in fibroblasts and blood cells derived from Alzheimer's disease patients. Here, using stable transfected SH-SY5Y cells overexpressing APP751wt (SY5Y-APP) we demonstrated that the expression of an unfolded p53 conformation compromised neuronal functionality. In particular, these cells showed (i) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 59 publications
0
30
0
1
Order By: Relevance
“…p53 is crucial for the induction of genes that lead to G1 arrest following DNA damage, enabling DNA repair. AD lymphocytes express an anomalous and detectable conformational state of p53 defined as a 'mutant like' conformation [57]. p53 adopts at least two tertiary structures in vivo, known as conformations: wild-type functionally active and mutant-type functionally inactive.…”
Section: Dysregulated Cell Cycle In Lymphocytesmentioning
confidence: 99%
“…p53 is crucial for the induction of genes that lead to G1 arrest following DNA damage, enabling DNA repair. AD lymphocytes express an anomalous and detectable conformational state of p53 defined as a 'mutant like' conformation [57]. p53 adopts at least two tertiary structures in vivo, known as conformations: wild-type functionally active and mutant-type functionally inactive.…”
Section: Dysregulated Cell Cycle In Lymphocytesmentioning
confidence: 99%
“…This antibody recognizes an epitope masked when the protein is in its native conformation and accessible only when the tertiary structure is unfolded [25,26,32,33]. Briefly, 100 µg of non-denaturated protein extracts, quantified with Bradford protein assay, or control peptide at different concentration ranging from 125 ng to 7,8 ng were coated on a plate overnight at 4°C.…”
Section: P53 Unfolded Isoform Analysismentioning
confidence: 99%
“…101 It showed that the formation of HNEp53 adducts did not affect the native conformation of p53, unlike nitration. The nitrated and so unfolded p53 directly decreases its pro-apoptotic activity and favors the survival of damaged neurons.…”
Section: Hne: a Serial Killermentioning
confidence: 99%